IMPLEMENTASI SIKAP MODERASI DALAM ORGANISASI ISLAM DI INDONESIA - Ahmad Aziz Mubaroq; Mohammad Nasrullah, Yufi; Ainissyifa, Hilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the literature on the Implementation of Moderation in Varios Differences in Islamic Organizations by offering an innovative persuasive approach to religious moderation to increase the sense of Moderation in living life.The reseach uses the Systematic Literatur Review approach with the she stages of determining the theme sarching,selecting literature, analyzing and interpreting, drafting preparation, and dissemination of result. The research conducted used 15 articles from a selection of 30 studies on four things, namely, implementation, challenges, innovation, and evaluation. Although various Islamic organizations, such as Nahdatul Ulama and Muhammadiyah, play an important role in promoting religious moderation through education, interreligious dialogue, and social activities, there is still a narrative of Extremism. Asystematic evaluation of these programs is aalso important to measure their effectiveness and impact on social harmony, so that it is hoped that it can create a more harmonious and respectful society in the midst of diversity.